Wired TV : Laboring Over an Interactive Future - Mann, Denise (Book collections on Project MUSE., 2014)
Wired TV looks at the post-network television industry's experiments with new forms of interactive storytelling that took place from 2005 to2010 as broadband was introduced into the majority of homes and the use of Facebook, YouTube, and Twitter soared. Essays address such issues as the networks' sporadic efforts to engage fans using transmedia storytelling, production inefficiencies, and the effect of corporate conglomeration on entrepreneurial creativity.